Nutrients Intake Is Associated with DNA Methylation of Candidate Inflammatory Genes in a Population of Obese Subjects - Bollati, Valentina; Favero, Chiara; Albetti, Benedetta; Tarantini, Letizia; Moroni, Alice; Byun, Hyang-Min; Motta, Valeria; Conti, Diana; Tirelli, Amedea; Vigna, Luisella; Bertazzi, Pier; Pesatori, Angela (Nutrients, 2014)
The aim of the present study was to evaluate the potential association between dietary nutrients and alterations in DNA methylation in a set of five candidate genes, including CD14, Et-1, iNOS, HERV-w and TNFα, in a population of overweight/obese subjects. We evaluated possible associations between gene methylation and clinical blood parameters, including total cholesterol (TC), low- and high-density lipoprotein cholesterol (LDL-C and HDL-C), triglyceride and homocysteine levels. We employed validated methods to assess anthropometric, clinical and dietary data, as well as pyrosequencing to evaluate DNA methylation of the five candidate genes in 165 overweight/obese subjects. There was no association between body mass index and DNA methylation of the five candidate genes in this group of subjects. Positive associations were observed between TNFα methylation and blood levels of LDL-C (β = 0.447, p = 0.002), TC/HDL-C (β = 0.467, p = 0.001) and LDL-C/HDL-C (β = 0.445, p = 0.002), as well as between HERV-w methylation and dietary intakes of β-carotene (β = 0.088, p = 0.051) and carotenoids (β = 0.083, p = 0.029). TNFα methylation showed negative associations with dietary intakes of cholesterol (β = −0.278, p = 0.048), folic acid (β = −0.339, p = 0.012), β-carotene (β = −0.332, p = 0.045), carotenoids (β = −0.331, p = 0.015) and retinol (β = −0.360, p = 0.008). These results suggest a complex relationship among nutrient intake, oxidative stress and DNA methylation.